The Impact of the Covid-19 Pandemic and Fintech Adoption on Financial Performance Moderating by Capital Adequacy - Nardi Sunardi; Firman Tatariyanto (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
The research objective was to determine the impact of the Covid-19 Pandemic and Fintech Adoption on Company Performance and Capital adequacy as a Moderating Variable in Indonesian Government Banking. This type of research is quantitative. Objects of Government Commercial Banks registered on the Indonesian Stock Exchange (IDX) in the 2012-2021 period. The data analysis method uses the panel data regression analysis method with the ordinary least squares (OLS) approach or the common effect model, fixed effect model, and random effect model. Data processing using the MS.Exel 2010 statistical software assistance application program includes the creation of tables and graphs for descriptive analysis with statistical processing with EVIEWS version 10. The results show that Fintech Adoption (FA) partially has a positive and significant effect on Financial Performance, the Covid-19 Pandemic 19 (COV) partially Has no negative effect on Financial Performance, Covid-19 Pandemic, and Fintech Adoption Simultaneously Has a Positive and Significant Effect on Financial Performance, Capital Adequacy (CAR) moderates Fintech Adoption (FA) on Financial Performance, Capital Adequacy (CAR) moderated the Covid-19 Pandemic (COV) on Financial Performance in Indonesian Government Banking